2018
DOI: 10.3390/nu10111701
|View full text |Cite
|
Sign up to set email alerts
|

Phloridzin, an Apple Polyphenol, Exerted Unfavorable Effects on Bone and Muscle in an Experimental Model of Type 2 Diabetes in Rats

Abstract: It is believed that apple fruits contain components with health-promoting effects, including some antidiabetic activity. One of the most known apple compounds is phloridzin, a glucoside of phloretin. Phloridzin and phloretin were reported to exert some favorable skeletal effects in estrogen-deficient rats and mice. The aim of the study was to investigate the effects of phloridzin on musculoskeletal system in rats with type 2 diabetes induced by a high-fat diet (HFD) and streptozotocin (STZ). The experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…In the present study, some flavonoid compounds have been detected for the first time in rosemary, viz., phlorizin ([M − H] − at m/z 435.13) in Soxhlet extract ( Table 4 ) and pectolinarigenin ([M − H] − at m/z 313.07) in all the extracts (T 1 –T 9 ). Phlorizin was earlier found in tree barks of the Rosaceae family, and the studies indicated high antidiabetic property of the drug [ 36 ]. Pectolinarigenin was also reported before in rosemary as dimethoxyflavone with similar fragment ions, and it was found to have potent anti-inflammatory and anticancer properties [ 31 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, some flavonoid compounds have been detected for the first time in rosemary, viz., phlorizin ([M − H] − at m/z 435.13) in Soxhlet extract ( Table 4 ) and pectolinarigenin ([M − H] − at m/z 313.07) in all the extracts (T 1 –T 9 ). Phlorizin was earlier found in tree barks of the Rosaceae family, and the studies indicated high antidiabetic property of the drug [ 36 ]. Pectolinarigenin was also reported before in rosemary as dimethoxyflavone with similar fragment ions, and it was found to have potent anti-inflammatory and anticancer properties [ 31 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to other reports, we observed increased random blood glucose level as well as the levels of fasting serum glucose, serum fructosamine, total cholesterol, and triglycerides. Moreover, induction of the type 2 diabetes resulted in the HOMA-IR increase and QUICKI decrease [32,35,54,[56][57][58]66]. There were also changes in the oxidative stress-related parameters in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…13 Phloridzin is a glycoside of phloretin, which is an established inhibitor of sodium glucose cotransporter (SGLT) to attenuate the hyperglycemia through inhibition of glucose reabsorption in intestine and/or kidney. 15 Stattic is a pharmacological inhibitor of STAT3, which could be used both in vitro and in vivo. 13 To investigate the interaction between adropin and STAT3, Stattic (ab120952, Abcam, Cambridge, UK) at indicated doses (1 mg/kg/day or 2 mg/ kg/day) or vehicle were intravenously administered to the other groups of STZ-diabetic rats for 7 days.…”
Section: Animal Experimentsmentioning
confidence: 99%